Partial PEGylation of superparamagnetic iron oxide nanoparticles thinly coated with amine-silane as a source of ultrastable tunable nanosystems for biomedical applications. Issue 2 (16th December 2016) - Cano, Manuel; Núñez-Lozano, Rebeca; Lumbreras, Rocío; González-Rodríguez, Verena; Delgado-García, Alberto; Jiménez-Hoyuela, José Manuel; de la Cueva-Méndez, Guillermo
Abstract : We describe a simple and low cost method to fabricate structurally and colloidally ultrastable water-soluble SPIONs that can be easily functionalized for a range of applications. Abstract : The development of superparamagnetic iron oxide nanoparticle (SPION)-based diagnostic and therapeutic nanosystems holds a promise of revolutionizing biomedicine, helping to solve important unmet clinical needs. Such potential will only be fulfilled if appropriate methods for SPION production and for their subsequent tailoring to specific applications are established, something that remains challenging. Here, we report a simple and low cost method to fabricate structurally and colloidally ultrastable, water soluble SPIONs. We used thermal decomposition to produce SPIONs of the highest quality, which were then thinly coated with an amine-silane derivative by ligand exchange, conferring hydrophilicity and great structural stability on the nanoparticles. Subsequent partial covalent occupancy of surface amine groups with polyethyleneglycol (PEG) was carried out to give them excellent colloidal stability, whilst still leaving reactive anchoring points for further functionalization. The correct composition and physicochemical properties of our PEGylated SPIONs and their precursors were confirmed using a broad range of analytical techniques, and we also demonstrated the biocompatible character of the resulting nanoparticles, as well as their suitability as T 2 MRI contrast agents in vivo . Finally, using a near infra-red fluorophore, we also confirmed that these SPIONs are amenable to further tuning, to adapt them to a wide range of applications or to optimize their performance in particular settings. In summary, our work provides a novel and robust method for the production of SPIONs that can be used as a tunable platform for the development of smart diagnostic and therapeutic nanosystems.